2013
DOI: 10.4236/ijg.2013.43057
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Tectonic Record of Strain Buildup and Stress Release across the Andean Forearc along the Gulf of Guayaquil-Tumbes Basin (GGTB) near Ecuador-Peru Border

Abstract: Gravimetric and geologic data show that the reactivation of the Neogene Interandean depression and/or the ~75 -65 Ma ophiolite suture into the modern dynamic of the Andes controlled the Gulf of Guayaquil Tumbes basin (GGTB) location and evolution during the past 1.8 -1.6 Myr at least. Depending on whether the remobilization occurred along the interandean depression or the ophiolite suture, the GGTB evolved trough pure or simple shear mechanisms, respectively. Because the GGTB exhibits an along strike tectonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…The black continuous lines are main crustal fault systems shown in Figure . Discontinued lines in the Gulf of Guayaquil area are detachments from Bourgois []. Pentagons represent historical epicenters relocated by Beauval et al [].…”
Section: Construction Of a New Seismic Source Zones Model For Ecuadormentioning
confidence: 99%
See 4 more Smart Citations
“…The black continuous lines are main crustal fault systems shown in Figure . Discontinued lines in the Gulf of Guayaquil area are detachments from Bourgois []. Pentagons represent historical epicenters relocated by Beauval et al [].…”
Section: Construction Of a New Seismic Source Zones Model For Ecuadormentioning
confidence: 99%
“…The origin and precise depth distribution of the cluster is not yet resolved. These large events could have ruptured the subduction megathrust [ Suarez et al ., ] or continental slope detachments in the Gulf of Guayaquil [ Bourgois , ], although von Huene et al [] and Bourgois et al [] favor a rotational landslide origin for similar detachments identified south of Talara without the release of M w ≥ 7 equivalent seismic energy.…”
Section: Construction Of a New Seismic Source Zones Model For Ecuadormentioning
confidence: 99%
See 3 more Smart Citations